Rhodium(III)-catalyzed hydroamination of aromatic terminal alkynes with anilines - Kumaran, Elumalai (2013)
The dinuclear Rh(III) species [Cp*RhCl2]2 catalyzes the hydroamination reaction between an aromatic terminal alkyne (ArCCH) and an aniline (Ar′NH2), in the presence of a salt additive, to afford the ketimine Ar′N═C(Me)(Ar). A reaction pathway has been proposed on the basis of experimental and computational studies.